Stability and Hopf bifurcation of a delayed reaction–diffusion predator–prey model with anti-predator behaviour - Liu, Jia; Zhang, Xuebing (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we study the dynamics of a delayed reaction–diffusion predator–prey model with anti-predator behaviour. By using the theory of partial functional differential equations, Hopf bifurcation of the proposed system with delay as the bifurcation parameter is investigated. It reveals that the discrete time delay has a destabilizing effect in the model, and a phenomenon of Hopf bifurcation occurs as the delay increases through a certain threshold. By utilizing upperlower solution method, the global asymptotic stability of the interior equilibrium is studied. Finally, numerical simulation results are presented to validate the theoretical analysis.
Keywords: delay; stability; Hopf bifurcation; antipredator